DIAGNÓSTICO TURÍSTICO PARA LA RESERVA NATURAL LOS HACHALES DEL CANTÓN EL PANGUI, PROVINCIA DE ZAMORA CHINCHIPE. - Medina Chalán, Jaime Javier (2015)
In recent years Ecuador has considered tourism as a strategy for local development, due to the different territorial potential, the natural, cultural and social wealth in order to project the development from the standpoint of environmental conservation and cultural wealth social. The dynamism and capacity development of tourism today has rated as one of the most important economic activities of the country, hence the importance of gathering information on tourist resources of the country is evident, allowing progress plan tourist destinations in a sustainable way, as well as to determine the existence of natural and cultural attractions. This study is focused on gathering information from the Natural Reserve of the Pangui Hachales Canton province Zamora Chinchipe, in order to facilitate decision-making about future strategies and have a tool to evaluate the success or failure of plans, programs and projects. The diagnosis ultimately the starting point for all tourism planning process is established. So above the development of the present work it aims to develop the collection of information that will serve as a starting point for tourism planning and booking a direct source of information to make decisions about future projects that may be constituted focused on developing tourism potential. Hence and to comply with the thematic focus was raised specific objectives: Determine the base of the Natural Reserve of the Pangui Hachales Canton line; Identify key existing tourist attractions the Hachales Nature Reserve; and propose 6 strategies for tourism development for the Natural Reserve of the canton Hachales the Pangui. Par meeting the objectives was unavoidable use various methods and techniques; for the first objective was taken as reference the Manual for Business Management of Protected Areas of Ecuador, proposed by the Ministry of Environment which aims to strengthen the management objectives of protected areas, specifically the G section focuses considered Diagnosis or assessment on the state of the protected area, where the following analysis was performed; Integrity analysis or state of conservation values; Analysis of threats and opportunities for conservation values; Analysis of social and economic function area Analysis area management. To fulfill the second objective methodology of the Ministry of Tourism (Mintur), which was the development of chips Survey of Information Sheets Sheets Summary Ranking and where it was determined the existence of the attractions was applied; Nature reserve the Hachales, Los achos, Chontacuros or Mayones, Rio Zamora and the Shuar Community Quimi. Finally to comply with the third specific objective analytical method it was applied and based on the information obtained on the SWOT matrix that led to proposing possible tourism development strategies framed in the current situation of the reserves was developed. Based on the achievement of the objectives it is concluded that the Hachales nature reserve has great tourism potential with many attractions that are not touristically exploited either by lack of infrastructure, signaling and trained people to attend to tourists; also intervened the poor dissemination of this place.